Synthesis and physicochemical properties of oligonucleotides built with either alpha-L or beta-L nucleotides units and covalently linked to an acridine derivative. - Asseline, U (1991)
Modified deoxynucleosides 2'-deoxy-beta-L-uridine, beta-L-thymidine, alpha-L-thymidine, 2'-deoxy-beta-L-adenosine and 2'-deoxy-alpha-L-adenosine were synthesized and assembled as homooligomers, respectively: octa-beta-L-deoxyuridylates, octa beta-L and alpha-L-thymidylates and tetra beta-L and alpha-L-deoxyadenylates. These unnatural oligomers were then substituted with an acridine derivative. The binding studies of these modified oligonucleotides with D-ribo- and D-deoxyribopolynucleotides were carried out by absorption spectroscopy. While beta-L-d(Up)8m5Acr, beta-L-(Tp)8m5Acr, alpha-L-(Tp)8m5Acr did not interact with poly(rA) and poly(dA), beta-L-d(Ap)4m5Acr and alpha-L-d(Ap)4m5Acr did form double and triple helices with poly(rU) and poly(dT), respectively. Their stability towards nuclease digestion was studied through comparison with that of octa-beta-D-thymidylate and tetra beta-D-deoxyadenylate covalently linked to an acridine derivative. One endonuclease (nuclease P1 from Penicillium citrinum) and two exonucleases (a 3'-exonuclease from Crotalus durissus venom and a 5'-exonuclease extracted from calf thymus) were employed. beta-L- and alpha-L-oligomers demonstrate a high resistance toward nuclease digestion.